Photocatalytic concrete for NOx abatement: Supported TiO2 efficiencies and impacts. (February 2019) - Yang, Lu; Hakki, Amer; Zheng, Li; Jones, M. Roderick; Wang, Fazhou; Macphee, Donald E.
Abstract: The potential of TiO2 -based photocatalysts in mitigating the effects of environmental pollutants is evident in the scientific literature but the large-scale implementation of photocatalytic concretes still appears limited, despite the current global concerns over urban NOx pollution. Improvements in cost-effectiveness are required to enhance the case for a photocatalyst-modified infrastructure and this must address catalyst efficiency, catalyst loading and performance durability. This paper compares photocatalytic efficiencies of supported TiO2 on mortar surfaces with the more conventional TiO2 dispersed in mortar. The influences of environmental conditions, such as NO concentration and flow rate, UVA light intensity and relative humidity, on photocatalytic performance are also investigated using photonic efficiency as an indicator. The supported TiO2 shows greater degradation of NOx (De-NOx), at about 9 times higher than TiO2 powder dispersed in the mortar, ca. 150 times higher utilization efficiency, than that of TiO2 in traditional photocatalytic mortar (with 5% loading). Graphical abstract: Unlabelled Image Highlights: Supported TiO2 shows greater utilization efficiency than that of TiO2 in mortar. Binding durability of supported TiO2 in mortar surface depends on its exposed depth. Environmental conditions influences on photocatalytic performance are presented. NO concentration, flow rate and relative humidity are main factors to NOx removal.